2017
DOI: 10.1007/s10546-017-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Observing and Simulating Wind-Turbine Wakes During the Evening Transition

Abstract: Wind-turbine-wake evolution during the evening transition introduces variability to wind-farm power production at a time of day typically characterized by high electricity demand. During the evening transition, the atmosphere evolves from an unstable to a stable regime, and vertical stratification of the wind profile develops as the residual planetary boundary layer decouples from the surface layer. The evolution of wind-turbine wakes during the evening transition is examined from two perspectives: wake observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 67 publications
1
41
0
Order By: Relevance
“…CWEX-13 campaign took place between late June and early September 2013 in a wind farm in central Iowa, the same wind farm studied in previous CWEX campaigns; however, CWEX-13 focused on a part of the wind farm that is different from what is discussed in Rajewski et al (2013), Rhodes and Lundquist (2013), Mirocha et al (2015), and Lee and Lundquist (2017). The region exhibits strong diurnal cycles of atmospheric stability and frequent nocturnal low-level jets (Vanderwende et al, 2015).…”
Section: Cwex-13 Observational Datasetmentioning
confidence: 99%
“…CWEX-13 campaign took place between late June and early September 2013 in a wind farm in central Iowa, the same wind farm studied in previous CWEX campaigns; however, CWEX-13 focused on a part of the wind farm that is different from what is discussed in Rajewski et al (2013), Rhodes and Lundquist (2013), Mirocha et al (2015), and Lee and Lundquist (2017). The region exhibits strong diurnal cycles of atmospheric stability and frequent nocturnal low-level jets (Vanderwende et al, 2015).…”
Section: Cwex-13 Observational Datasetmentioning
confidence: 99%
“…This campaign was a component of the larger CWEX project, which explored the interactions of wind turbines with crops, surface fluxes, and near-surface flows in different atmospheric stability regimes in flat terrain (Rajewski et al, 2013). Research facilitated by the CWEX projects include diurnal changes in observed turbine wakes (Rhodes and Lundquist, 2013), turbine interactions with moisture and carbon dioxide fluxes , LES modelling of turbine wakes in changing stability regimes , nocturnal low-level jet (LLJ) occurrences (Vanderwende et al, 2015), diurnal changes of the microclimate near wind turbines (Rajewski et al, 2016), multiple-wake interactions (Bodini et al, 2017), the evolution of turbine wakes during the evening transition (Lee and Lundquist, 2017), and coupled mesoscalemicroscale modelling (Muñoz-Esparza et al, 2017).…”
Section: Observationsmentioning
confidence: 99%
“…The vertical levels are further stretched beyond the boundary layer. In past research involving the WRF WFP scheme, the selections of vertical resolution within the rotor layer include 9-18 m in , about 10-16 m in Volker et al (2015), about 15 m in Fitch et al (2012Fitch et al ( , 2013a and , about 20 m in Miller et al (2015) and Vautard et al (2014), about 22 m in Lee and Lundquist (2017), and about 40 m in Eriksson et al (2015) and Jiménez et al (2015). Moreover, the Mellor-Yamada-Nakanishi-Niino (MYNN) level 2.5 planetary boundary layer (PBL) scheme is required for the WFP in the WRF model version 3.8.1 .…”
Section: Modellingmentioning
confidence: 99%
See 2 more Smart Citations